2017
DOI: 10.11646/zootaxa.4226.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Systematics of some calloporid and lacernid Cheilostomata (Bryozoa) from coastal South Korean waters, with the description of new taxa

Abstract: Six species in two families of Cheilostomata-Calloporidae and Lacernidae-are described from the southern coasts of the Korean Peninsula, resulting in a new distributional record and four new species to the Korean fauna. Further, Woosukia n. gen. is described, based on an existing species. Two species names (Crassimarginatella crassimarginata and Arthropoma cecilii) are deleted from the Korean faunal list owing to previous misidentification, with the net result that the Korean cheilostome fauna is increased to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 578 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…These differences were also noted by Reverter-Gil & Souto (2021) who introduced the new species Cradoscrupocellaria severoi for some of the colonies while leaving others unassigned. The colonies of Arthropoma cecilii (the only species of this genus known from the Mediterranean) reported from the Tyrrhenian Sea by Chimenz Gusso et al (2014) possibly belong to a different species, as suggested by Min et al (2017). Another example is Bugula neritina consisting of three cryptogenic species only recognizable through molecular analyses (Fehlauer-Ale et al, 2014), two of which presumably occur in the Mediterranean (Tanduo et al, 2021).…”
Section: Future Challenges Relating To Improved Technologies Global C...mentioning
confidence: 98%
“…These differences were also noted by Reverter-Gil & Souto (2021) who introduced the new species Cradoscrupocellaria severoi for some of the colonies while leaving others unassigned. The colonies of Arthropoma cecilii (the only species of this genus known from the Mediterranean) reported from the Tyrrhenian Sea by Chimenz Gusso et al (2014) possibly belong to a different species, as suggested by Min et al (2017). Another example is Bugula neritina consisting of three cryptogenic species only recognizable through molecular analyses (Fehlauer-Ale et al, 2014), two of which presumably occur in the Mediterranean (Tanduo et al, 2021).…”
Section: Future Challenges Relating To Improved Technologies Global C...mentioning
confidence: 98%
“…The genus appears closest to Crassimarginatella Canu, 1900 in its affinities. Gordon (2014) and Min et al (2017) have discussed the range of morphological variation in Crassimarginatella, especially that expressed by ooecia and avicularia (see also Harmelin, 1973), concluding that, while splitting the genus appeared to have merit, more information was needed. The type species, Crassimarginatella crassimarginata (Hincks, 1880a), has, inter alia, avicularia with a stout pivot bar, basal pore-chambers and a tatiform ancestrula with spines, all features shared with the type species of Quitocallopora gen. nov.…”
Section: Remarksmentioning
confidence: 99%